The Influence of Backscattering Angle on Full-duplex Underwater Wireless Optical Communication - HAN Biao; LIU Bin; ZHANG Yu; MA Lin; LIU Yutong; KANG Yongqiang (Guangtongxin yanjiu)
【Objective】In bidirectional Underwater Wireless Optical Communication (UWOC) system, backscattering is one of the major factors which affect its stability. In a full-duplex UWOC system, such noise could be removed by optical filter in the receiver. However, because the transmission wavelength of filter would be “blue shift” with incident angle of light, the backscattering angle will affect the noise suppression performance.【Methods】In this paper, a theoretical model is constructed by Monte Carlo method to qualitatively study the angle distribution characteristics of backscattering noise and its influence on UWOC performance.【Results】The results show that, angle distribution of backscattering noise is relatively dispersed in full-duplex UWOC system with large divergence angle and filed. It has a great influence on the equipment whose transmitting wavelength is smaller than the receiving one. In engineering applications, without affecting the link establishment efficiency, equipment structural complexity, and effective communication distance of the UWOC system, the impact can be mitigated by appropriately reducing the communication transmission angle, receiver aperture, and field of view, increasing the spacing between the transmitter and receiver in the communication equipment, and enlarging the wavelength interval of the bidirectional optical signals. Using this method, a full-duplex UWOC system is built with about 50° transmitting angle and field based on 450 and 520 nm blue-green light. In the communication distance of 2.2~13.2 m, the file transmitting rates are 89.6 and 84.8 Mbit/s for the two transmission links respectively.【Conclusion】The research results in this paper are helpful to design a full-duplex UWOC system with large transmitting and receiving angles.